Development of special purpose sausage recipes based on blood processed products - Haschuk, Olexandra; Moskaluyk, Oksana; Guralevich, Anna (My University, 2020)
In the scientific work in the development of sausage recipes, turkey meat was selected, and the use of blood protein Globin Vepro Gel 95 HV in the composition of protein-fat emulsion (BJE) and whole blood to increase the iron content in the product for the prevention and treatment of anemia. According to the results of experimental studies of organoleptic and functional-technological indicators of model minced meat, it was found that the addition to the minced meat BZE based on globin protein in the amount of 40 % by weight of minced meat and the addition of whole blood with a mass fraction of 5 and 7 %. У науковій роботі при розробленні рецептур сосисок обрано м'ясо індиків, а також запропоновано використання білку крові Глобін Vepro Gel 95 HV у складі білково-жирової емульсії (БЖЕ) та цільну кров з метою підвищення вмісту заліза у продукті для профілактики та лікування анемії. За результатами експериментальних досліджень органолептичних і функціонально-технологічних показників модельних фаршів встановлено, що додавання до фаршу БЖЕ на основі білка глобіну у кількості 40 % до маси фаршу та додавання цільної крові з масовою часткою крові 5 та 7% відповідно дозволить отримати фаршеву систему з якісними характеристиками.
Keywords: сосиски; дитяче харчування; білково-жирова емульсія; sausages; baby food; protein-fat emulsion; кафедра технології м’яса і м’ясних продуктів